2014
DOI: 10.1038/nrn3665
|View full text |Cite|
|
Sign up to set email alerts
|

Functional MRI-based lie detection: scientific and societal challenges

Abstract: Functional MRI (fMRI)-based lie detection has been marketed as a tool for enhancing personnel selection, strengthening national security and protecting personal reputations, and at least three US courts have been asked to admit the results of lie detection scans as evidence during trials. How well does fMRI-based lie detection perform, and how should the courts, and society more generally, respond? Here, we address various questions — some of which are based on a meta-analysis of published studies — concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
175
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(209 citation statements)
references
References 56 publications
16
175
0
18
Order By: Relevance
“…To the extent that imaging cannot provide help with high-stake problems, the public should be protected from claims that it can. For example, a seemingly 'scientific' method for detecting lies or diagnosing psychiatric disorders 66,97 has a strong appeal to the general public who cannot be expected to appreciate the gap between what is claimed and what is established fact.…”
Section: Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent that imaging cannot provide help with high-stake problems, the public should be protected from claims that it can. For example, a seemingly 'scientific' method for detecting lies or diagnosing psychiatric disorders 66,97 has a strong appeal to the general public who cannot be expected to appreciate the gap between what is claimed and what is established fact.…”
Section: Boxmentioning
confidence: 99%
“…Lie detection is one example that has been pursued in legal contexts, although it has not so far been admitted into US courts and has yet to demonstrate validity, reliability or resistance to countermeasures outside of the laboratory 66 . Another application concerns pain: brain-based biomarkers for pain would help discriminate real suffering from malingering-a pivotal issue in many lawsuits-and have been admitted as evidence in at least one US case 67 .…”
Section: Human Neuroscience In the Courtroommentioning
confidence: 99%
“…One of the most significant open questions is whether memory decoding is vulnerable to "countermeasures": strategies deployed to mask memory signals and "beat" detection tests (Farah et al, 2014). Rissman et al (2010) reported indirect evidence suggesting a vulnerability to strategic goal states, because the ability to detect previously encountered from novel faces was reduced to near chance when participants' memory was implicitly, rather than explicitly, probed.…”
Section: Introductionmentioning
confidence: 99%
“…Other objections mounted by neuroskeptics include problems with the neuroimaging methodology itself and doubts about the interpretation or overinterpretation of results. For a discussion of neuroskepticism as well as a set of counterarguments, see, for example, Farah et al (2014), and Rachul and Zarzeczny (2012).…”
mentioning
confidence: 99%